Epistemological differences in the discussion of the interpersonal theory of suicide: A reply to the response. Issue 2 (7th February 2021) - Hjelmeland, Heidi; Knizek, Birthe Loa
Abstract: This paper is a reply to Smith and colleagues' response to our critique of the interpersonal theory of suicide (IPTS). They believe that we mischaracterize and misinterpret aspects of the IPTS. Here, we argue that the problem rather seems to be that we are discussing the IPTS from two different epistemological "planets."